The Influence of Workload, Time Pressure, and Interpersonal Relationships on the Performance of Makassar Heritage Office Employees - Sendi Lesmana; M. Yusuf Alfian Rendra Anggoro; Sri Wahyuni (Journal Social Society, 2025)
Employees of the Balai Harta Peninggalan (BHP) Makassar face significant challenges in carrying out legal administrative duties, particularly due to the vast scope of the work area, which covers 13 regions in Eastern Indonesia, and the limited number of human resources. High workloads, time pressure in task completion, and the dynamics of interpersonal relationships have the potential to affect overall employee performance. In light of this urgency, this study aims to analyze the influence of workload, time pressure, and interpersonal relationships on employee performance at BHP Makassar. This research employed a descriptive quantitative approach using a survey method. Data were collected through observation, literature review, and the distribution of closed-ended questionnaires to the entire population of 34 employees, thus eliminating the need for sampling techniques. The research instruments were validated and tested for reliability before analysis. The data were analyzed using multiple linear regression with the aid of SPSS version 27. The findings indicate that both partially and simultaneously, workload, time pressure, and interpersonal relationships have a positive and significant influence on employee performance. A proportionally distributed workload, effectively managed time pressure, and conducive interpersonal relationships significantly contribute to improving employee productivity and work quality. These findings provide important implications for institutional management in designing work policies that support employee performance improvement and offer a basis for further research exploring additional variables in the context of public sector organizations.